Electoral systems and female representation in politics: Evidence from a regression discontinuity - Jarosław Kantorowicz; Monika Köppl-Turyna (Agenda Austria, 2020)
This work looks at the policies aimed at promoting female participation in local legislative bodies using a series of changes to electoral law in Poland. Using an exogenous population threshold dividing municipalities into ones with proportional and ones with majoritarian elections, we estimate the effect of the electoral system on female representation. Moreover, we use difference-in-discontinuities to look at the effect of an introduction of a female quota on female participation in local councils. Contrary to the literature for the national elections, we find that more females are elected to local councils in the majoritarian system. We link this observation to countering party bias in list placements and lower costs of electoral participation in the majoritarian system. We find that the female quota has a strong positive effect on the percentage of females in the local council. It increases the pool of female candidates and has a positive effect on their list placements. It does not, however, create spillovers to neighboring regions.
Keywords: D72; B52; 330; electoral rules; forms of government; female representation; regression discontinuity; difference in discontinuities